Penerapan pendekatan realistic mathematics education (RME) berbantuan teknologi interaktif untuk meningkatkan kemampuan pemecahan masalah matematis siswa kelas VIII - Lestari, Anjani Putri; Fitriani, Nelly; Bernard, Martin (IKIP Siliwangi, 2025)
The purpose of this study was to determine whether the improvement in mathematical problem-solving abilities of eighth-grade students whose learning implemented the Realistic Mathematics Education (RME) approach assisted by interactive technology was better than students with regular learning. The research method used was a quantitative method using a quasi-experimental research type with a Pretest Posttest Nonequivalent Control Group design. The population of this study was all eighth-grade students of SMP Negeri 4 Cimahi with a research sample of students in class VIII H as the experimental class and class VIII K as the control class. The research instrument used a problem-solving ability test. The test result data were analyzed using the Mann Whitney test. The study showed that the mathematical problem-solving abilities of students whose learning implemented the RME approach assisted by interactive technology were better than students who used regular learning.